2017
DOI: 10.1057/s41295-017-0100-3
|View full text |Cite
|
Sign up to set email alerts
|

The short-term and long-term effects of institutional reforms on party system nationalization

Abstract: The impact of institutions on party system nationalization has traditionally been examined in a cross-national fashion. However, while in some cases institutional reforms may be expected to immediately affect party nationalization, in others, changes might take place over subsequent elections. In this paper, we argue that reforms affecting mainly elite coordination -such as decentralization-will take a longer time to have an impact on party system nationalization than reforms related to the mechanical effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…2016). In accordance with the present results, previous studies have demonstrated that Croatia has more localized party system than Serbia (Bochsler, 2010c;Golosov, 2016;Schakel, 2017). However, our study introduced a new methodology based on electoral volatility indices and this result demonstrates that method is capable of estimating nationalization and localization metrics using different spatial units of analysis which wasn't explored in previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…2016). In accordance with the present results, previous studies have demonstrated that Croatia has more localized party system than Serbia (Bochsler, 2010c;Golosov, 2016;Schakel, 2017). However, our study introduced a new methodology based on electoral volatility indices and this result demonstrates that method is capable of estimating nationalization and localization metrics using different spatial units of analysis which wasn't explored in previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Notably, policy and governance are the most contributed ones of all the literature on institutional reform. Simon and Guinjoan (2017) modelled impacts of electoral reforms on party system nationalization to conclude on institutional reforms" positive impacts all over the European countries in post-WWII era. Benz and Sonnicksen (2018) revise institutional reforms of German federalism from the point of view of its influence on the quality of decision-making procedure and find specific triggers that cause unexpected effects beyond the conventional procedures of decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%